Improving crop nutrient efficiency through root architecture modifications. Issue 3 (17th November 2015) - Li, Xinxin; Zeng, Rensen; Liao, Hong
Abstract: Improving crop nutrient efficiency becomes an essential consideration for environmentally friendly and sustainable agriculture. Plant growth and development is dependent on 17 essential nutrient elements, among them, nitrogen (N) and phosphorus (P) are the two most important mineral nutrients. Hence it is not surprising that low N and/or low P availability in soils severely constrains crop growth and productivity, and thereby have become high priority targets for improving nutrient efficiency in crops. Root exploration largely determines the ability of plants to acquire mineral nutrients from soils. Therefore, root architecture, the 3‐dimensional configuration of the plant's root system in the soil, is of great importance for improving crop nutrient efficiency. Furthermore, the symbiotic associations between host plants and arbuscular mycorrhiza fungi/rhizobial bacteria, are additional important strategies to enhance nutrient acquisition. In this review, we summarize the recent advances in the current understanding of crop species control of root architecture alterations in response to nutrient availability and root/microbe symbioses, through gene or QTL regulation, which results in enhanced nutrient acquisition. Abstract : Root is essential for plant growth, nutrient and water acquisition and symbiosis with microflora in soils. Here, we summarized the recent advances in crop species' control of root architecture alterations in response to nutrient availability and root/microbe symbioses, through gene or QTL regulation, which results in enhanced nutrient efficiency.